Diseño para la implementación del departamento de talento humano en la Cooperativa de Servicios Educacionales “Juan Montalvo” de la ciudad de Loja. - Armijos Chalan, Diego Israel (2018)
The Human Resources Administration is one of the areas most affected by the recent changes taking place in the modern world. Companies realized that people are the central element of their nervous system because they introduce intelligence in business and rationality in decisions. Treating people as organizational resources is wasting talent and productive mind. Therefore to provide this new vision of people, today we talk a bout Human Resource Management and not Human Resources. The cooperative was created on May 14, 1999, has 26 members and sponsors three projects: The "Juan Montalvo" Private Educational Unit, the "Isidro Ayora Cueva" Distance School and the Juan Montalvo Hi gher Technological Institute, and has: 400 students enrolled, 43 teachers, 6 administrative and 1 directives. To carry out the work, applied research was used. This type of research will be applied in the educational services cooperative "Juan Montalvo" of the city of Loja, and will be for the personnel that work, that is to say the manager, administrative and teachers. The Cooperative does not currently have a person specialized in Human Talent Management, to manage in an adequate way the human resources of the Cooperative and if they do it is empirically, due to that they have many deficiencies in relation to human talent.The creation of a Human Talent Management Department is justified.